Building research capacity in clinical practice for social workers: a training and mentorship approach. (2nd January 2020) - Withington, Tania; Alcorn, Neil; Maybery, Darryl; Goodyear, Melinda
ABSTRACT: Objective: This paper describes a Training and Mentoring Program, designed to enhance research capacity for social workers based in community and inpatient settings in Australia. Method: Twenty-one social workers participated in the multiday training and follow-up mentoring program (small group and individual) over a 24-month period. Outlined is a mixed-method quasi-experimental evaluation of the approach. Results: Quantitative data showed an increase in self-reported research capacity including knowledge, confidence, behaviour and satisfaction. The mentoring approach appeared to be a crucial component for participants – for their engagement with research, willingness or ability to bypass perceived and real hurdles, and completion of an individual research project. A significant barrier to research was a lack of available research time during their clinical role and forcing participants to complete research projects in their own time. Additionally, personal challenges such as health and family commitments on time available to undertake research after hours impacted on engagement and research project completion. Discussion: Social workers are critical contributors to practice-based evidence development in health and mental health settings. However, many report a lack of knowledge, confidence and skills in service evaluation and research. The findings demonstrate that social workers are keen to take on practitioner-research roles, that research capacity is enhanced through training particularly with follow-up mentoring to support individual research project development and implementation, and that large system changes need to occur to support social workers to engage in research activities in their work context.